The Existence of Islamic Boarding Schools During The Covid-19 Pandemic - Susanto Susanto; Ayu Desrani (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to thoroughly discuss the existence of implementing Islamic boarding schools and teaching and learning activities during the pandemic and post-pandemic. This research is qualitative research with a descriptive method. The population of this study was 15 teachers in 5 Islamic boarding schools in South Sumatra. Data were collected using questionnaires and interviews through telephone booths and then analyzed using the Milles and Huberman method with the stages of data collection, data presentation, and then drawing conclusions. The results in this study indicate that during the covid-19 pandemic or even post-covid-19, Islamic boarding schools always exist to carry out all routine Islamic boarding school activities. Learning is still done offline or face-to-face. And other activities continue to run as they should while still implementing health protocols. And it will be a challenge for Islamic boarding schools after the pandemic to make changes and creativity so that learning and activities are not monotonous.